Public attitudes toward the use of human induced pluripotent stem cells: insights from an Italian adult population - Elia, Noemi; Prinelli, Federica; Peli, Valeria; Conti, Silvia; Barilani, Mario; Mei, Cecilia; Castaldi, Silvana; Lazzari, Lorenza (Frontiers in public health, 2024)
Human induced pluripotent stem cells (hiPSCs), derived from reprogrammed adult somatic cells, hold significant promise for disease modelling, personalized medicine, drug discovery, and regenerative therapies. Public awareness and understanding of hiPSCs are crucial for advancing research in this field. However, limited data exists on the general population's knowledge and attitudes toward their use. This study aimed to assess the awareness and perceptions of hiPSCs among Italian adults through a web-based survey conducted via the EUSurvey platform, using a snowball sampling approach. The survey included demographic information and mandatory questions on knowledge, awareness, and concerns regarding hiPSC technology, with responses collected on a 3-point scale. Statistical analysis was performed using chi-squared tests, with significance set at ≤ 0.05. Out of 1874 respondents, the majority were aged 18-35 years (40.5%), female (63.4%), and university-educated (67.2%). Among those familiar with hiPSCs (54.1%, = 1,201), 95.3% expressed willingness to donate blood samples for hiPSC generation to treat individuals with incurable diseases. Concerns about current research and therapeutic applications were low (less than 20%), but nearly half of the respondents were hesitant or opposed to the use of hiPSCs in animal experiments and their commercialization by pharmaceutical companies. Increased skepticism was observed in older, less educated, religious individuals, and those who were not blood donors. Overall, the Italian public shows strong support for hiPSC-based therapies, though reservations exist around specific ethical and economic issues. These findings underscore the importance of addressing public concerns through targeted educational campaigns, not only in Italy but globally, to foster a more informed and supportive environment for advancing stem cell research and its clinical applications worldwide. Similar studies have been conducted in Japan, the United States, and Sweden, but there remains a need for all countries to engage with their citizens to better understand how stem cell research is perceived locally. Such engagement is crucial for guiding international strategies in personalized medicine and regenerative therapies, ensuring that emerging technologies are met with both ethical integrity and public trust.